Successful treatment of a keloid on the upper lip by trepanation and radiotherapy: a case report - Xianghui Li; Yong Wei; Zhuren Ruan; Gao Wei; Zhijian Yao (Journal of Dermatological Treatment)
Purpose: Keloid tissue represents an abnormal proliferation of fibroblasts, typically resulting from skin injury. These lesions can lead to significant physiological dysfunction and aesthetic concerns, particularly when located on the face. Traditional treatments, such as intralesional injections, laser therapy, and surgical excision, have shown limited efficacy and are associated with high recurrence rates.Materials and methods: In a recent case, a 19-year-old male with a keloid on the upper lip did not respond to local injections of triamcinolone acetonide (TAC) or carbon dioxide ablative fractional resurfacing laser therapy.Results: A combined treatment approach involving trepanation and superficial radiotherapy successfully flattened the keloid tissue, with no recurrence observed during a 3-year follow-up period.Conclusions: This case underscores the potential efficiency and safety of combined therapeutic interventions and contributes valuable evidence towards the development of novel treatment strategies for keloids.